Sexual trauma among girls in educational settings: intersectional identities and trauma-informed care - Herring, Jennifer Etesse (Routledge, 2025)
This book uses an intersectional lens to explore the lived experiences of sexually traumatized girls in school. It provides a deep understanding of the students' experiences, viewed through the prism of their multiple identities